1994
DOI: 10.1111/j.1365-2621.1994.tb08120.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Membrane‐Sterilized Bovine Immunoglobulins Aseptically Added to UHT Milk

Abstract: Lyophilized immunoglobulin (IgG) of 56% purity isolated from Cheddar cheese whey was reconstituted with distilled water to a protein content of 60-70 mg/mL. The solution was membrane-sterilized (0.2 pm) and aseptically injected into cartons of UHT milk. This method could be used for fortjfication of UHT products without denaturing IgG. Concentration of IgG remained constant in milk stored at 4, 25 and 35°C over 5 mo. However, when stored at 25 and 35"C, the milk thinned probably due to residual enzymes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…2) suggested a higher thermoresistance for IgA than for IgG below 69ЊC, experiments not shown demonstrated an extremely slow rate for IgG denaturation at 65ЊC. These results were consistent with those reported by Fukumoto et al (1994), who found a D 65 value for IgG more than 4 times greater than what we obtained for IgA. Li-Chan et al (1995) obtained D values lower than ours for IgG heated in different media.…”
Section: Denaturation Of Immunoglobulinssupporting
confidence: 92%
“…2) suggested a higher thermoresistance for IgA than for IgG below 69ЊC, experiments not shown demonstrated an extremely slow rate for IgG denaturation at 65ЊC. These results were consistent with those reported by Fukumoto et al (1994), who found a D 65 value for IgG more than 4 times greater than what we obtained for IgA. Li-Chan et al (1995) obtained D values lower than ours for IgG heated in different media.…”
Section: Denaturation Of Immunoglobulinssupporting
confidence: 92%
“…To determine a suitable range of holding temperatures and times in this work, preliminary experiments were performed and also other authors' results (Fukumoto et al 1994;Dominguez et al 1997) were referred to. Dominguez et al showed that the antigen-binding activity of IgG could survive a heat treatment of 63 Á658C/60 min, and the temperature range of 69 Á818C was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…So the quantification of IgG in dairy products was heavily dependent on the degree of denaturation of the protein. There was considerable variation in literature values, such as 1 (Fukumoto et al 1994;Chan et al 1995;Li-Chan et al 1995), 1.2 (Zhang & Guo 2001), 1.5 (Law 1995;Dominguez et al 1997;Mainer et al 1999) or 2 (Lucisano et al 1994) for the reaction orders of thermal denaturation of IgG, the denaturation of IgG was therefore believed to involve several simultaneous reactions with different temperature dependence. These differences also resulted from the different systems employed, for example, concentration of proteins or acidity can affect the conformation of IgG.…”
Section: Introductionmentioning
confidence: 95%
“…Bovine milk is a good medium for functional products containing, for example, specific antibodies. The shelf‐life of these products can be prolonged by membrane filtration (10) or by fermentation processing. In our study with UHT milk, the pH remained stable for up to 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously described composition of IP and CP (20, 22), further analyses were carried out for total IgA, IgM, IGF‐1, TGF‐β1 and TGF‐β2 (10, 31). IgG was analysed with gel filtration chromatography according to Syväoja and Korhonen (37).…”
Section: Methodsmentioning
confidence: 99%